MENINGKATKAN MINAT BELAJAR ANAK DENGAN MENGGUNAKAN TEKNIK KOLASE DARI BAHAN PLASTIK BEKAS JAJANAN DI TK NEGERI 1 PEMBINA GUNUNGSITOLI SELATAN T.P. 2014/2015 - PURBA, NATALINA; LAROSA, MARIANA (Jurnal Pendidikan Usia Dini, 2016)
The purpose of this study is to increase children's interest in learning to use traditionallearning collage technique of plastic scrap materials snacks. This study begins October 13, 2014and ending November 21, 2014, with a research subject as many as 15 children. This study wasconducted in TK Negeri Pembina Gunungsitoli 1 South. Research Model action Deny Setiawan,where I cycle consists of four components, covering planning, action, observation and reflection.This study applies two cycles consisting of 10 actions. Analysis of data using qualitative methods.The results of research studies have occurred from the first cycle, 46.68% of children, includingless well, as much as 26.66%, including 26.66% of criteria as well as very good, while on thesecond cycle has been a significant increase that 20% of children included both criteria and 80%including excellent. Researchers suggest the success of a program requires the role of thecompetent institution, Master sole spearhead to make innovations in improving the quality ofeducation to the students.